2017
DOI: 10.3389/fimmu.2017.01685
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Glycodelin in Cancer Development and Progression

Abstract: Glycodelin is a kind of glycoprotein expressed in secretory endometrium, pregnancy deciduas, and amniotic fluid originally, which is vital for the maintenance of normal human reproductive activities. Recent researches have reported that glycodelin is specifically expressed in various malignancies, including female-specific cancers such as endometrial cancer, ovarian cancer and breast cancer, and non-gender specific cancers including lung cancer, and colon cancer, and glycodelin expression correlates with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 95 publications
1
28
0
5
Order By: Relevance
“…The Hu-FEDS hypothesis also predicts that tumour cells employ the same carbohydrate functional groups used in the pregnant uterus to evade the human immune response [52]. Consistent with this concept, hCG and other pregnancy-related glycoproteins are often upregulated in tumour cells [54][55][56][57].…”
Section: Discussionmentioning
confidence: 88%
“…The Hu-FEDS hypothesis also predicts that tumour cells employ the same carbohydrate functional groups used in the pregnant uterus to evade the human immune response [52]. Consistent with this concept, hCG and other pregnancy-related glycoproteins are often upregulated in tumour cells [54][55][56][57].…”
Section: Discussionmentioning
confidence: 88%
“…Considering these aspects, vascular endothelial cadherin (VEC) has gained interest in the research field of ovarian cancers due to its role in activating endothelial genes and triggering stability-related genes thus exerting a direct influence on the ovarian carcinoma vasculature [30]. Also, glycodelin is an important promoter of tumor angiogenesis in ovarian cancer and influences the differentiation and function of immune cells such as T and B cells, dendritic cells, macrophages and NK cells [31]. Under these circumstances, glycodelin may become an effective target in antiangiogenic therapy and immunotherapy in ovarian cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it is worth noting that GdA expression is observed not only in healthy tissues of the reproductive tract, but also in certain types of cancer: lung, breast, endometrium, ovaries, and melanoma cells [28,57,64,65,82]. It has been shown that GdA can be used as a biomarker to track the progression of a tumor, as has been shown in non-small cell lung cancer, recurrence or metastatic spread [11]. Understanding the regulation of the glycodelin expression may lead to the development of new therapeutic approaches, with the help of which it will be possible to weaken the system of protection of the tumors themselves.…”
Section: Place Of Glycodelin Synthesismentioning
confidence: 90%
“…Neither glycosylation nor sialylation of glycodelin does not impair the ability of monocytes to chemotaxis. Recombinant GdA binds to a specific protein receptor in monocytes, but the corresponding receptor is not detected on the surface of T or B cells [11]. Further study of the GdA action mechanism established that on the surface of cells of the monocyte-macrophage lineage, the binding protein for glycodelin is the L-selectin molecule.…”
Section: гликоделины в регуляции иммунитетаmentioning
confidence: 99%